ISLAMIC PSYCHOTHERAPY APPROACH TO IMPROVE THE WELL-BEING OF ADOLESCENTS WITH PHYSICAL DISABILITIES AT THE BUDI PERKASA CENTER - Alin, Luthfiah; Akbar Setiawan, Tri Kasda; Rasmanah, Manah (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
Adolescents with physical disabilities often face psychological distress that impacts their mental well-being, such as low self-esteem, isolation, and a loss of meaning in life. This study aims to determine the effectiveness of an Islamic psychotherapy approach in improving the psychological well-being of adolescents with physical disabilities. The subject at the Budi Perkasa Center in Palembang. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman model. The results indicate that Islamic psychotherapy through dhikr (remembrance of God), muhasabah (religious reflection), and religious counseling positively contributed to increasing self-acceptance, inner peace, and meaning in life for the client. This approach is considered effective for implementation in a social rehabilitation setting based on religious values.